Social Enterprises in Brazil and Poland: Comparative Analysis - Marcelo T Okano; Graziela Bizin Panza; Iwona Otola (International Journal of Supply Chain Management, 2019)
The main objective of this study is to verify how social enterprises through recycling cooperatives are developing reverse logistics under the theoretical lenses of economic, social and environmental value creation in Brazil and Poland. For the accomplishment of this research qualitative approach was applied, and the method used was multiple case studies, where more than one object of study was considered, with an exploratory and descriptive nature. During the interviews with the managers of the social enterprises in Brazil and in Poland semi-structured script was used. In order to verify the economic, social and environmental value creation the triple layer business model of Osterwalder and Pigneur (2011) and Joyce and Paquin (2016) was applied. Among the results it can be highlighted the creation of value beyond financial value, social inclusion through the generation of work and income, cleanliness of the municipality and appropriated disposal of recyclable materials, ecological value through reductions of environmental impact and ecological regenerative positive value in both countries, Brazil and Poland.